Comparison of Legal Aspects of Consumer Protection in E-commerce Transactions and TikTok Shop in Indonesia - Judijanto, Loso; Solapari, Nuryati; Karim, Asma; Febryani, Evy (Westscience Press, 2024)
Consumer protection in the digital age presents unique challenges and opportunities, particularly in the context of emerging platforms like TikTok Shop. This study undertakes a comparative analysis of the legal aspects of consumer protection in e-commerce transactions and TikTok shops in Indonesia. Through a normative approach, key similarities, differences, challenges, and opportunities are identified, shedding light on the evolving regulatory landscape and its implications for consumers, businesses, and policymakers. Findings highlight the need for adaptive regulation, enhanced enforcement mechanisms, industry collaboration, and consumer empowerment to ensure a fair, transparent, and accountable digital commerce ecosystem.